Crystallographic Orientation Dependence of Nitrogen Mass Transport in Austenitic Stainless Steel - Teresa Moskalioviene; Arvaidas Galdikas (Metals, 2020)
The lattice stress-induced diffusion of nitrogen and hydrogen in austenitic stainless steel, taking place during nitriding in nitrogen/hydrogen plasma, is analyzed in the presented work. Stress-induced diffusion has an anisotropic nature and depends on the orientation of the crystal lattice. However, during simulations, it is not enough to take into account only the anisotropy of stress-induced diffusion, since this leads to contradictory results when comparing with experimental data. The problem is the surface concentration of nitrogen. Processes on the steel surface such as adsorption, desorption and heterogeneous chemical reactions are also very important. In the presented work, it is shown that these surface processes also have anisotropic natures, and it is very important to take this anisotropy into account during simulations. The influence of anisotropic surface processes on austenitic steel nitriding is analyzed in this study. It is shown that the nitrogen diffusion is anisotropic due to the effects of the anisotropic stress gradient and the anisotropic effects on the steel surface.